A DEM based tool for the safety analysis of masonry gravity dams - Bretas, E. M. (2014)
A numerical model for analysis of masonry gravity dams based on the discrete element method is presented. The dam and the rock foundation are represented as block assemblies, using elementary 3- and 4-node blocks. Complex block shapes are obtained by assembling the elementary blocks into macroblocks, allowing the model to be applied in various situations ranging from equivalent continuum to fully discontinuum analysis. A contact formulation was developed, which represents the interaction between macroblocks in terms of contacts established between elementary blocks, based on an accurate edge-edge approach. The main numerical aspects of the model are described, addressing in particular the contact creation and update procedures, and the numerical devices that support an efficient explicit solution algorithm. An application to the safety evaluation of an existing masonry dam is discussed, including stress analysis in the structure, and the assessment of sliding failure mechanisms, involving different paths in the vicinity of the dam-rock interface.